Tuning defect-related optical bands by channeling implants in semiconductors. (29th December 2022) - Azarov, Alexander; Galeckas, Augustinas; Ling, Francis Chi-Chung; Kuznetsov, Andrej
Abstract: Ion implantation is an excellent method to introduce defects into semiconductors, extending their functionalities in a controllable way. Herein, we investigated an option to use crystallographically aligned implants as an additional route to control the balance between optically active defects, selecting ZnO as a test material. The optical data were correlated with the structural analysis confirming the formation of different dominating crystalline defects in samples implanted along and off [0001] direction. Specifically, we demonstrated that different proportions in the contents of the extended and point defects in the initial as-implanted states of these samples, lead to prominent variations in the defect-related luminescence upon annealing. As such, we conclude that channeling implants may have an added value in the functionalization of defects in semiconductors, e.g. to tune specific spectral contents in the defect-related emission bands.